Availability, Cyst Characteristics and Hook Morphology of Echinococcus granulosus Isolates from Livestock (Cattle, Sheep and Goats) in Central Punjab, Pakistan - Mustafa, Irfan; Shahbaz, Mussarat; Asif, Saira; Khan, Mobushir Riaz; Saeed, Umer; Sadiq, Faiza; Simsek, Sami (Kafkas Univ, Veteriner Fakultesi Dergisi, 2015)
Cystic Echinococcosis (CE) is a zoonotic infection caused by larval (metacestode) stages of cestodes belonging to the genus Echinococcus and the family Taeniidae. The aim of current study was to determine the availability and organ placement of hydatid cysts in some ruminants of Pakistan and to study of rostellar hooks morphology of protoscoleces of E. granulosus. A total of 2803 animals comprising 925 sheep, 939 goats and 939 cattle (n=) from both sexes were examined to find out the prevalence of hydatid cysts in different regions of Central Punjab from January to December 2013. The overall prevalence of hydatidosis was determined as 3.24%, 2.44% and 2.44% in examined sheep, goats and cattle, respectively. The localization of hydatid cysts in the livers of infected sheep, goats and cattle was found as 1.4%, 1.17% and 1.17%, respectively while lung localizations were determined as 1.83%, 1.27% and 1.27% in the same order. Among the 33, 25 and 30 examined hydatid cysts in sheep, goats and cattle, 8 (24.2%), 11 (33.3%), 8 (24.2%), 6 (18.1%); 9 (36%), 9 (36%), 4 (16%), 3 (12%) and 10 (33.3%), 11 (36.6%), 4 (13.3%), 5 (16.6%) were characterized as fertile, sterile, calcified and under-developed, respectively. The total number of hooks on protoscoleces was 28.68 +/- 3.80 (sheep origin), 26.0 +/- 2.59 (goat origin) and 27.70 +/- 1.11 (cattle origin). In conclusion our investigation revealed that availability of hydatid cysts is still significantly higher among all examined livestocks.
Pakistan’ın Pencap eyaletindeki Çiftlik hayvanlarında (sığır, koyun ve keçi) Echinococcus granulosus izolatlarının mevcudiyeti, kist karakteristiği ve Çengel morfolojisi
Keywords: Hydatid cyst; Protoscoleces; Availability; Cattle; Sheep; Goat; Pakistan